PENGARUH KOMPETENSI, DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL PADA PT. SUKSES BAHARI LOGISTIC SURABAYA - Desi Rahmawati; Khoirul Abidin (Bussman Journal : Indonesian Journal of Business and Management, 2022)
This studys aims to examine and analyzes the effect of competence and organizational commitmen at PT. Success of Maritime Logistics Surabaya. The sampling techniques used in this research is saturated sampling (Census), with a total sampel of 35 respondent. The analiysis technique used in this research is multiple linears regressions analysis technique. The result of the analysis show that competence and organizational commitment simultaneously have a significant effect on managerial performance at PT. Success Bahari Logistics Surabaya, Competence (X1) partially has a significan effect on managerial performances at PT. Success of Maritime Logistics Surabaya. Organizational Commitment (X2) partially has a significant effects on managerial performances at PT. Success of Maritime Logistics Surabaya